Perspectives of Online News Media on Extreme Poverty and Regional Budget Policy Response - Indiahono, Dwiyanto; Satyawan, Darmanto Sahat (Ministry of Home Affairs, 2023)
A report of residents living in extreme poverty level in Banyumas Regency required local government’s response through Extreme Poverty Reduction Program. Such poverty alleviation program consequently necessitated swift provision from the regional budget (Anggaran Pendapatan dan Belanja Daerah/APBD). On the other hand, no budget had been allocated for the program during the budget year and the APBD was limited. The purpose of this study is to examine the responses of regional budget policy to the extreme poverty issue based on online news articles related to the subject. The study was conducted using content analysis methods and systematic literature reviews. The results show that the Banyumas government's response in addressing extreme poverty issue is relatively satisfactory. The local government responded with a regional budget policy by funding the program through Unexpected Expenditure (Belanja Tidak Terduga/BTT) budget item. Part of APBD, BTT was allocated as non-cash extreme poverty alleviation expenditure, while cash social assistance was to be sought to from the provincial and central government. Local governments do not have adequate budgetary capacity to independently finance extreme poverty alleviation programs and therefore require major support from the central and/or provincial government. A synergy between local, provincial and central governments is thus needed to better manage regional extreme poverty alleviation initiatives.